Realization of meat qualities of Black Motley bull-calves against the background of immunoprophylaxis with biological Preparations - G. Semenov, Vladimir; I. Kosyaev, Nikolay; Yu. Lavrentyev, Anatoly; A. Larionov, Gennady; V. Evdokimov, Nikolay; M. Toboyev, Gerald; A. Nikitin, Dmitry; D. Nazarov, Sergey (International Journal of Engineering and Technology, 2018)
For the first time on the basis of complex studies the zootechnical expediency of the developed biological preparations Prevention-N-A and Prevention-N-E in beef production technology for the realization of bioresource potential of meat qualities of Black Motley bull-calves was scientifically and experimentally proved. Activation of the growth and development of bull-calves in the periods of growth, rearing and fattening was established against the background of biopreparations, which resulted in higher slaughter and meat qualities of the carcasses and, as a consequence, in a higher yield of valuable cuts: brisket and sirloin by 6.1 and 4.0 kg (P < 0,01-0,001), rump by 2,6 and 1,7 kg (P <0,05-0,01) and thick flank by 8,6 and 7,1 kg (P <0,001) (compared with the control group). The largest content of highest-quality meat came from the carcasses of the bull calves of the 1st (27.8 Â± 0.72 kg) and the 2nd (26.7 Â± 0.58 kg) test groups: 3.5 and 2.4 kg more, respectively, as compared with the control group (24,3 Â± 0,73 kg), and also from their cuts: brisket and sirloin - 0,9 and 0,7 kg more, respectively, rump - 0,5 and 0,3 kg, and thick flank â€“ 2,3 and 1, 5 kg (P <0.05-0.001). The high quality of meat carcasses by organoleptic, biochemical and spectrometric indicators and, consequently, the safety of the tested preparations was proved. It was found that biological preparations lead to the realization of bioresource potential of the organism due to activation of haemopoiesis, cellular and humoral factors of non-specific resistance (with a more pronounced Prevention-N-A effect). The novelty of the data obtained is confirmed by the patents of the Russian Federation for invention No. 2602687 and No. 2622765 registered in the Public Register of Inventions of the Russian Federation on October 26, 2016 and June 19, 2017, respectively.Â Â